Yawning reduces facial temperature in the high-yawning subline of Sprague-Dawley rats. Issue 1 (December 2017) - Eguibar, Jose; Uribe, Carlos; Cortes, Carmen; Bautista, Amando; Gallup, Andrew
Abstract Background Yawning is a stereotyped behavior that enhances blood flow to the skull, and the resulting counterflow has been hypothesized as a mechanism for brain cooling. Studies have shown that yawns are strongly associated with physiological and pathological conditions that increase brain temperature, and that they are followed by equivalent decreases in brain temperature. However, measured reductions in cranial or facial temperatures following yawning have yet to be reported, to our knowledge. To accomplish this, we used a subline of Sprague-Dawley rats that yawn at a much greater rate (20 yawns/h) than do outbred Sprague-Dawley rats (2 yawns/h). Results Using an infrared camera, we effectively evaluated thermal changes in the cornea and concha of these rats before, during, and after yawns. The maximum temperature in both regions significantly decreased 10 s following yawns (concha: −0.3 °C, cornea: −0.4 °C), with a return to basal temperatures after 20 s. Conclusions This study is the first clear demonstration of yawning-induced thermal cooling on the surface of the face, providing convergent evidence that this behavior plays a functional role in thermoregulation. As other studies have demonstrated that yawning is capable of reducing cortical brain temperature, our current data support the idea that yawning functions as a thermoregulator, affecting all structures within the head.